Glass-ceramics
A crystallized glass with specific composition and crystalline structure addresses the issue of scratches on cover glasses by enhancing fracture toughness and transparency, making it suitable for use in devices like smartphones.
Patent Information
- Application Number
- JP2020076603
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-04-23
- Publication Date
- 2024-12-18
- Estimated Expiration
- 2040-04-23
AI Technical Summary
Cover glasses, especially smartphone cover glasses, are prone to surface scratches due to high illuminance and parallel light, reducing display visibility, and existing crystallized glass is not transparent enough for use as a cover glass.
A crystallized glass composition comprising SiO2, Al2O3, B2O3, MgO+ZnO, CaO+SrO+BaO, P2O5+TiO2+ZrO2, Na2O+K2O, and optionally Li2O, with specific crystallinity, thickness, and transparency, containing crystals like gahnite, forsterite, anorthite, zirconolite, rutile, and zirconia, and a compressive stress layer, enhancing fracture toughness and transparency.
The solution provides a crystallized glass with high fracture toughness, excellent transparency, and improved scratch resistance, suitable for use as a cover glass in devices like smartphones, with a fracture toughness value of 0.75 MPa m0.5 or higher and visible light transmittance of 50% or more.
Smart Images

Figure 0007602188000001
Abstract
Description
[Technical field]
[0001] The present invention relates to glass-ceramics. [Background technology]
[0002] Mobile phones, digital cameras, PDAs (personal digital assistants), etc. are becoming more and more popular. For these applications, cover glass is used to protect the touch panel display (see Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2006-083045 A Summary of the Invention [Problem to be solved by the invention]
[0004] Cover glass, especially that of smartphones, is often used outdoors, where light with high illuminance and parallelism makes surface scratches easily noticeable, reducing the visibility of the display. Therefore, it is important to improve the scratch resistance of glass. Increasing the fracture toughness value is considered to be a useful method for improving scratch resistance. Increasing the fracture toughness value makes it difficult for the surface to be scratched, and even if a hard scratch is created, the width and depth of the scratch can be reduced.
[0005] Glass ceramics, in which crystals are precipitated in glass, is known as glass with a high fracture toughness value.
[0006] However, crystallized glass is inferior to amorphous glass in terms of transparency and is therefore not suitable for use as a cover glass.
[0007] An object of the present invention is to provide crystallized glass having high fracture toughness and excellent transparency. [Means for solving the problem]
[0008] The crystallized glass of the present invention is characterized by containing, by mass%, 40-70% SiO2, 5-40% Al2O3, 2-25% B2O3, 0-15% MgO+ZnO, 0-20% CaO+SrO+BaO, 0-8% P2O5+TiO2+ZrO2, 1-20% Na2O+K2O, and 0-6% Li2O, having a crystallinity of 1-50%, a thickness of 0.8 mm, and an average visible light transmittance of 50% or more at a wavelength of 380-780 nm. Here, "MgO+ZnO" means the combined amount of MgO and ZnO, "CaO+SrO+BaO" means the combined amount of CaO, SrO and BaO, "P2O5+TiO2+ZrO2" means the combined amount of P2O5, TiO2 and ZrO2, and "Na2O+K2O" means the combined amount of Na2O and K2O.
[0009] It is preferable that the crystallized glass of the present invention contains substantially no As2O3 or PbO.
[0010] The crystallized glass of the present invention preferably contains one or more crystals selected from the group consisting of gahnite (ZnAl2O4), forsterite (Mg2SiO4), anorthite (CaAl2Si2O8), zirconolite (CaZrTi2O7), rutile (TiO2), and zirconia (ZrO2).
[0011] The crystallized glass of the present invention preferably has an average crystallite size of 1 μm or less.
[0012] The crystallized glass of the present invention preferably has a compressive stress layer formed on the surface.
[0013] The crystallized glass of the present invention has a fracture toughness value of 0.75 MPa m 0.5 The "fracture toughness value" herein refers to a value measured by the Indentation Fracture method (IF method) in accordance with JIS R1607, and is the average value of 10 measurements.
[0014] The crystallized glass of the present invention preferably has a refractive index (nd) of 1.6 or less and an Abbe number (νd) of 50 or more.
[0015] The crystallized glass of the present invention preferably has a bending strength of 100 MPa or more and a drop height of 5 mm or more. Here, the "drop height" refers to the maximum height at which the glass retains its original shape without breaking when a 50 mm x 50 mm glass plate is placed on a granite surface plate and a 53 g weight with a Vickers indenter attached to the tip is dropped vertically from a specific height onto the glass.
[0016] The crystallized glass of the present invention is characterized in that one or more types of crystals selected from gahnite (ZnAl2O4), forsterite (Mg2SiO4), anorthite (CaAl2Si2O8), zirconolite (CaZrTi2O7), rutile (TiO2), and zirconia (ZrO2) are precipitated, the crystallization degree is 1 to 50%, the thickness is 0.8 mm, and the average visible light transmittance at a wavelength of 380 to 780 nm is 50% or more. Effect of the Invention
[0017] According to the present invention, it is possible to provide crystallized glass having high fracture toughness and excellent transparency. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The crystallized glass of the present invention contains, by mass%, SiO2 40-70%, Al2O3 5-40%, B2O3 2-25%, MgO+ZnO 0-15%, CaO+SrO+BaO 0-20%, P2O5+TiO2+ZrO2 0-8%, Na2O+K2O 1-20%, and Li2O 0-6%, has a crystallinity of 1-50%, a thickness of 0.8 mm, and a visible light average transmittance of 50% or more at a wavelength of 400-780 nm. In the following description, unless otherwise specified, "%" means mass%.
[0019] First, the reason for limiting the composition of the crystallized glass as described above will be explained.
[0020] SiO2 is a component that forms the skeleton of glass. The content of SiO2 is 40 to 70%, and preferably 45 to 55%. If the content of SiO2 is too low, the weather resistance tends to deteriorate significantly. On the other hand, if the content of SiO2 is too high, the melting property of glass tends to deteriorate.
[0021] Al2O3 is a component that enhances ion exchange performance. It is also a component of gahnite (ZnAl2O4) and anorthite (CaAl2Si2O8). The content of Al2O3 is 5 to 40%, preferably 6 to 37%, 7 to 35%, 8 to 30%, 9 to 28%, and particularly preferably 10 to 25%. If the content of Al2O3 is too low, coarse crystals are likely to precipitate. Also, crystallization becomes difficult. On the other hand, if the content of Al2O3 is too high, the melting property of the glass is likely to deteriorate.
[0022] B2O3 has the effect of increasing the meltability of glass and lowering the liquidus temperature. The content of B2O3 is 2 to 25%, preferably 4 to 22%, 6 to 20%, and particularly preferably 8 to 18%. If the content of B2O3 is too low, not only the meltability of glass is poor, but also the liquidus temperature becomes high, and the raw glass is easily devitrified during molding. On the other hand, if the content of B2O3 is too high, crystallization becomes difficult. Also, coarse crystals are easily precipitated.
[0023] MgO and ZnO are components that enhance the meltability of glass. The content of MgO+ZnO is 0-15%, preferably 0.1-13%, 1-12%, 2-10%, and particularly preferably 2.5-8%. If the content of MgO+ZnO is too low, the meltability of glass tends to deteriorate. On the other hand, if the content of MgO+ZnO is too high, the liquidus temperature tends to rise and the degree of crystallinity tends to become too high.
[0024] MgO is also a component of forsterite (Mg2SiO4). The content of MgO is preferably 0 to 20%, 1 to 15%, 2 to 10%, and particularly preferably 2.5 to 8%. If the content of MgO is too high, the liquidus temperature is likely to rise and the degree of crystallinity tends to become too high.
[0025] ZnO is also a component of gahnite (ZnAl2O4). The ZnO content is preferably 0 to 20%, 0.1 to 20%, 0.2 to 18%, 0.3 to 16%, 0.4 to 14%, 0.5 to 12%, and particularly preferably 0.6 to 10%. If the ZnO content is too high, the liquidus temperature is likely to rise and the degree of crystallinity tends to become too high.
[0026] CaO, SrO, and BaO are components that enhance the melting property of glass. CaO+SrO+BaO is 0-20%, preferably 0.1-18%, 0.2-16%, 0.3-14%, 0.4-12%, and particularly preferably 0.5-10%. If the CaO+SrO+BaO content is too high, crystallization becomes difficult. Also, coarse crystals tend to precipitate. CaO is also a component of anorthite (CaAl2Si2O8) and zirconolite (CaZrTi2O7), and its content is preferably 0-20%, 0.1-18%, 0.2-16%, 0.3-14%, 0.4-12%, and particularly preferably 0.5-10%. The SrO content is preferably 0 to 20%, 0.1 to 18%, 0.2 to 16%, 0.3 to 14%, or 0.4 to 12%, and particularly preferably 0.5 to 10%.The BaO content is preferably 0 to 20%, 0.1 to 18%, 0.2 to 16%, 0.3 to 14%, or 0.4 to 12%, and particularly preferably 0.5 to 10%.
[0027] P2O5, TiO2 and ZrO2 are nucleating agents. P2O5+TiO2+ZrO2 is 0-8%, preferably 0.1-8%, 0.2-7%, 0.3-6%, 0.4-5%, and particularly preferably 0.6-4.5%. If the amount of P2O5+TiO2+ZrO2 is too small, crystallization becomes difficult. On the other hand, if the amount of P2O5+TiO2+ZrO2 is too large, the melting property of the glass tends to deteriorate.
[0028] P2O5 is also a component that reduces the crystallite size. The content of P2O5 is preferably 0 to 10%, 0.1 to 9%, 0.3 to 8%, 0.5 to 6%, 0.5 to 5%, and particularly preferably 1 to 4%. If the content of P2O5 is too high, the glass becomes more prone to devitrification, making it difficult to melt and mold the glass. In addition, the chemical durability is easily reduced.
[0029] TiO2 is also a component of rutile (TiO2). The content of TiO2 is preferably 0 to 10%, particularly 0.1 to 5%. If the content of TiO2 is too high, the crystal growth rate becomes fast, making it difficult to control the crystallinity, and the devitrification becomes strong, making it difficult to melt and mold the glass.
[0030] ZrO2 is also a component of zirconia (ZrO2). The content of ZrO2 is preferably 0 to 8%, particularly 0.1 to 5%. If the content of ZrO2 is too high, devitrification becomes strong, making it difficult to melt and mold the glass.
[0031] Na2O and K2O are components that enhance the meltability of glass, and are also essential components for ion exchange treatment. Na2O+K2O is 1 to 20%, and preferably 2 to 15%. If the Na2O+K2O content is too low, the meltability of the glass may be poor and the ion exchangeability may decrease. On the other hand, if the Na2O+K2O content is too high, crystallization may become difficult. The Na2O content is preferably 1 to 20%, and more preferably 2 to 15%. The K2O content is preferably 1 to 20%, and more preferably 2 to 15%.
[0032] Li2O is a component that enhances the melting property of glass and can be involved in ion exchange treatment. The content of Li2O is 0 to 4%, and preferably 0.1 to 3.5%, 0.2 to 3%, 0.3 to 2.5%, 0.4 to 2%, and particularly preferably 0.6 to 1.5%. If the content of Li2O is too high, the liquidus temperature is likely to rise and the crystallite size tends to become too large.
[0033] The crystallized glass article of the present invention may contain the following components in the glass composition in addition to the above components.
[0034] SnO2 is a clarifier. The content of SnO2 is preferably 0 to 3%, 0.05 to 2%, 0.1 to 1.5%, and particularly preferably 0.15 to 1.25%. If the content of SnO2 is too high, the glass becomes more devitrified, making it difficult to melt and mold the glass. In addition, the crystal growth rate increases, and transparency tends to decrease.
[0035] CeO2 not only improves solubility, but also acts as an oxidizing agent, reducing the amount of Fe in the total Fe impurity. 2+ It is a component that suppresses the increase in CeO2 and increases the transparency of the crystallized glass. The CeO2 content is preferably 0 to 0.5%, 0.05 to 0.5%, and particularly preferably 0.1 to 0.3%. If the CeO2 content is too high, 4+ The coloring due to the oxidation may become too strong, causing the crystallized glass to turn brown.
[0036] SO3 can be introduced from Glauber's salt. The effect of SO3 is to improve the solubility of the raw glass. It also acts as an oxidizing agent like CeO2, and its effect becomes more pronounced when it coexists with CeO2. The content of SO3 is preferably 0 to 0.5%, 0.02 to 0.5%, and particularly preferably 0.05 to 0.3%. If there is too much SO3, foreign crystals may precipitate, deteriorating the surface quality of the crystallized glass.
[0037] Since As2O3 and PbO are harmful, it is preferable that they are not substantially contained. Here, "substantially not contained" means that these components are not intentionally added to the glass, and does not mean that unavoidable impurities are completely excluded. More objectively, it means that the content of these components, including impurities, is 1000 ppm or less.
[0038] The crystallized glass of the present invention preferably has one or more crystals selected from gahnite (ZnAl2O4), forsterite (Mg2SiO4), anorthite (CaAl2Si2O8), zirconolite (CaZrTi2O7), rutile (TiO2), and zirconia (ZrO2) precipitated. The fracture toughness value of the crystallized glass is increased by precipitating gahnite (ZnAl2O4), forsterite (Mg2SiO4), anorthite (CaAl2Si2O8), zirconolite (CaZrTi2O7), rutile (TiO2), and / or zirconia (ZrO2). In addition, the chemical durability is increased by precipitating gahnite (ZnAl2O4), rutile (TiO2), and / or zirconia (ZrO2). In the present invention, the precipitation of crystals other than gahnite (ZnAl2O4), forsterite (Mg2SiO4), anorthite (CaAl2Si2O8), zirconolite (CaZrTi2O7), rutile (TiO2), and zirconia (ZrO2) is not excluded. Gahnite (ZnAl2O4), forsterite (Mg2SiO4), anorthite (CaAl2Si2O8), zirconolite (CaZrTi2O7), rutile (TiO2), and zirconia (ZrO2) are preferably the main crystals, but are not necessarily required to be the main crystals.
[0039] The crystallized glass of the present invention has a degree of crystallization of 1-50%, preferably 2-40%, 3-35%, 4-30%, and particularly preferably 5-20%. If the degree of crystallization is too low, the fracture toughness value tends to decrease. On the other hand, if the degree of crystallization is too high, the transmittance tends to decrease. In addition, when ion-exchanging, the ratio of the glass phase to be the object of ion-exchanging treatment is small, so that it is difficult to form a high compressive stress layer by ion-exchanging treatment.
[0040] The crystallite size of the crystallized glass of the present invention is preferably 1 μm or less, 0.5 μm or less, particularly 0.3 μm or less. If the crystallite size is too large, the transmittance is likely to decrease. The lower limit of the crystallite size is not particularly limited, but in reality, it is 1 nm or more.
[0041] The crystallized glass of the present invention has a thickness of 0.8 mm and an average visible light transmittance at a wavelength of 380 to 780 nm of 50% or more, preferably 55% or more, and particularly preferably 60% or more. If the transmittance is too low, it becomes difficult to use it as a cover glass for a smartphone.
[0042] The crystallized glass of the present invention has a whiteness L * It is preferable that the whiteness value is 50 or less, 40 or less, and particularly 30 or less. If the whiteness is too high, the transmittance is likely to decrease. * The values are as defined in JIS Z 8730.
[0043] The crystallized glass of the present invention has a fracture toughness value of 0.75 MPa m 0.5 More than 1MPa m 0.5 More than 1.1MPa m 0.5 If the fracture toughness value is too low, the glass surface is easily scratched. There is no particular upper limit to the fracture toughness value, but in reality, it is generally no more than 20 MPa m 0.5 The following is the result.
[0044] The crystallized glass of the present invention preferably has a refractive index (nd) of 1.6 or less, 1.59 or less, 1.58 or less, 1.57 or less, 1.56 or less, particularly preferably 1.55 or less. If the refractive index is too high, light scattering is likely to occur at the interface between the glass surface and air.
[0045] The crystallized glass of the present invention preferably has an Abbe number (νd) of 50 or more, 50.2 or more, 50.4 or more, 50.6 or more, 50.8 or more, particularly preferably 51 or more. If the Abbe number is too small, chromatic aberration is likely to occur in the displayed images and videos when used as a cover glass for a smartphone or the like.
[0046] The flexural strength of the crystallized glass of the present invention is preferably 100 MPa or more, 105 MPa or more, 110 MPa or more, particularly 120 MPa or more. If the flexural strength is too low, it is easy to break. The upper limit of the flexural strength is not particularly limited, but in reality, it is 2000 MPa or less.
[0047] The crystallized glass of the present invention is preferably dropped from a height of 5 mm or more, 7 mm or more, and particularly preferably 10 mm or more. If the drop height is too low, the glass becomes easily broken.
[0048] The crystallized glass of the present invention preferably has a strain point of at least 500° C., particularly at least 530° C. If the strain point is too low, there is a risk that the glass will deform during the crystallization step.
[0049] The crystallized glass of the present invention has a thermal expansion coefficient of 20 to 120×10 at 30 to 380° C. -7 / K, 30-110 x 10 -7 / K, especially 40-100×10 -7 / K. If the thermal expansion coefficient is too low, it becomes difficult to match the thermal expansion coefficient with the surrounding members, whereas if the thermal expansion coefficient is too high, the thermal shock resistance is easily reduced.
[0050] Next, the method for producing the crystallized glass of the present invention will be described.
[0051] First, glass raw materials are mixed to obtain a desired composition. The mixed raw material batch is then melted at 1400 to 1600°C for 8 to 16 hours and formed into a predetermined shape to obtain a crystallizable glass body. The forming can be performed by a well-known forming method such as a float method, an overflow method, a down-draw method, a roll-out method, or a mold press method. If necessary, a bending process or other process can be performed.
[0052] Next, the crystallizable glass body is heat-treated at 700 to 1100°C for 0.1 to 10 hours to precipitate gahnite (ZnAl2O4), forsterite (Mg2SiO4), anorthite (CaAl2Si2O8), zirconolite (CaZrTi2O7), rutile (TiO2), and / or zirconia (ZrO2) as precipitated crystals, thereby obtaining transparent crystallized glass. It is acceptable for crystals other than these six types to precipitate. The heat treatment may be performed only at a certain temperature, or may be held at two or more levels of temperature and heat-treated stepwise, or may be heated while applying a temperature gradient. In addition, crystallization may be promoted by applying or irradiating sound waves or electromagnetic waves.
[0053] The crystallized glass may then be ion-exchanged to further increase the fracture toughness. In ion exchange, the crystallized glass body is brought into contact with a molten salt adjusted to near the strain point temperature of the crystallized glass, thereby replacing the alkali ions (e.g., Na ions or Li ions) in the surface glass phase with alkali ions (e.g., K ions) that have a larger ionic radius. In this way, a compressive stress layer with a compressive stress value of 300 MPa or more and a compressive stress depth of 10 μm or more can be formed on the surface of the crystallized glass. The "compressive stress value" and "depth of the compressive stress layer" refer to values measured by microscopic laser Raman spectroscopy.
[0054] If necessary, surface processing such as film formation, mechanical processing such as cutting and drilling, etc. may be carried out before or after the ion exchange. EXAMPLES
[0055] The present invention will be described in detail below with reference to examples. Table 1 shows Examples 1 to 11 and Comparative Example 12.
[0056] [Table 1]
[0057] The crystallized glasses of Examples 1 to 11 and Comparative Example 12 were prepared as follows.
[0058] First, the batch raw materials prepared to have the composition shown in the table were put into a melting furnace and melted at 1500 to 1600°C. The molten glass material was then rolled and slowly cooled to produce crystallizable glass of 900 x 1200 x 7 mm. The crystallizable glass was heat-treated at the temperature shown in the table for 2 hours to obtain crystallized glass. Note that, for Comparative Example 12, no heat treatment was performed and no crystallization was performed.
[0059] Next, the crystallized glass was subjected to an ion exchange treatment by immersing it in a KNO3 molten salt maintained at 430°C for 4 hours, to obtain a chemically strengthened crystallized glass.
[0060] The crystallinity, average crystallite size, precipitated crystals, transmittance, fracture toughness, refractive index, Abbe number, flexural strength, drop height, and thermal expansion coefficient of the samples thus prepared were evaluated. The results are shown in Table 1.
[0061] The crystallinity, average crystallite size, and precipitated crystals were evaluated using an X-ray diffractometer (Rigaku Smart Lab, fully automated multipurpose horizontal X-ray diffractometer). The scan mode was 2θ / θ measurement, the scan type was continuous scan, the scattering and divergence slit width was 1°, the receiving slit width was 0.2°, the measurement range was 10-60°, the measurement step was 0.1°, and the scan speed was 5° / min. The precipitated crystals were evaluated using the analysis software installed in the package of the same model. The average crystallite size of the precipitated crystals was calculated using the measured X-ray diffraction peaks based on the Debeye-Scherrer method. The scan speed was 1° / min for the measurement to calculate the average crystallite size. The crystallinity was calculated based on the X-ray diffraction profile obtained by the above method, as follows: (integral intensity of the X-ray diffraction peak of the crystal) / (total integrated intensity of the measured X-ray diffraction)×100[%].
[0062] The average visible light transmittance in the wavelength range of 380 to 780 nm was measured using a crystallized glass plate with a thickness of 0.8 mm that was optically polished on both sides, using a spectrophotometer, a V-670 spectrophotometer manufactured by JASCO Corporation.
[0063] The fracture toughness value was measured 10 times by the Indentation Fracture method (IF method) in accordance with JIS R1607, and the average value was calculated.
[0064] The refractive index was measured using a Shimadzu KPR-2000 at the d-line (587.6 nm) of a helium lamp.
[0065] The Abbe number was calculated from the above d-line refractive index and the F-line (486.1 nm) and C-line (656.3 nm) refractive index values of a hydrogen lamp using the formula Abbe number (νd) = (nd-1) / (nF-nC). Shimadzu KPR-2000 was used for the measurement.
[0066] Flexural strength was measured using the three-point load method according to ASTM C880-78.
[0067] The drop height was determined by a drop test in which a 50 mm x 50 mm glass plate was placed on a granite surface plate, and a 53 g weight with a Vickers indenter attached to the tip was dropped vertically onto the glass from a specific height. The maximum height at which the glass retained its original shape without breaking was determined as the drop height.
[0068] The thermal expansion coefficient was measured using a crystallized glass sample processed to 20 mm×3.8 mmφ in a temperature range of 30 to 380° C. A Dilatometer manufactured by NETZSCH was used for the measurement.
[0069] Examples 1 to 11 of the present invention are crystallized glasses having a degree of crystallinity of 10 to 40%, a high transmittance of 52% or more, and a fracture toughness value of 1.1 MPa m 0.5 In addition, the fracture toughness value was increased to 2.8 MPa m by ion exchange treatment. 0.5 On the other hand, Comparative Example 12 was an amorphous glass, and the fracture toughness value was 0.7 MPa m 0.5 It was low. [Industrial Applicability]
[0070] The crystallized glass of the present invention is suitable as a cover glass for touch panel displays of mobile phones, digital cameras, PDAs (mobile terminals), etc. In addition to these applications, the crystallized glass of the present invention is expected to be used in applications requiring high fracture toughness and transparency, such as window glass, substrates for magnetic disks, substrates for flat panel displays, cover glass for solar cells, and cover glass for solid-state imaging devices.
Claims
1. In mass%, SiO 2 40-70%, Al 2 O 3 5-40%, B 2 O 3 2-25%, MgO+ZnO 0-15%, CaO+SrO+BaO 0-20%, P 2 O 5 + TiO 2 + ZrO 2 0.2-6%, Na 2 O+K 2 O 1-20%, Li 2 A crystallized glass containing 0-6% O, 0.1-6% P 2 O 5 and 0.1-5% ZrO 2 , having a crystallinity of 1-50%, a thickness of 0.8 mm and an average visible light transmittance of 50% or more at a wavelength of 380-780 nm.
2. In effect, As 2 O 3 2. The crystallized glass according to claim 1, which is free of PbO.
3. Gahnite (ZnAl 2 O 4 ), forsterite (Mg 2 SiO 4 ), anorthite (CaAl 2 S 2 O 8 ), zirconolite (CaZrTi 2 O 7 ), rutile (TiO 2 ), and zirconia (ZrO 2 3. The crystallized glass according to claim 1, wherein one or more types of crystals selected from the following are precipitated:
4. 4. The crystallized glass according to claim 1, wherein the average crystallite size is 1 μm or less.
5. 5. The crystallized glass according to claim 1, further comprising a compressive stress layer formed on the surface thereof.
6. Fracture toughness value is 0.75 MPa m 0.5 6. The crystallized glass according to claim 1, wherein the crystallized glass is a glass having a molecular weight of 1000 or more.
7. 7. The crystallized glass according to claim 1, wherein the refractive index (nd) is 1.6 or less and the Abbe number (νd) is 50 or more.
8. 8. The crystallized glass according to claim 1, which has a bending strength of 100 MPa or more and a drop height of 5 mm or more.
Citation Information
Patent Citations
Crystallized glass article and its production
JP1994009245A
Natural marble-like crystallized glass article and its production
JP1994024768A
Crystallized glass and its production
JP1997263424A
Translucent apatite glass ceramic
JP1999029342A
High rigidity glass ceramic substrate for information magnetic storage medium
JP2000187828A
